PERBANDINGAN HASIL PEMERIKSAAN HBA1C METODE BORONATE AFFINITY DAN NEPHELOMETRY PHOTOMETRY: COMPARISON OF HBA1C EXAMINATION RESULTS BY BORONATE AFFINITY METHOD AND NEPHELOMETRY PHOTOMETRY - Rizka Amalia; Christina Destri Wiwis Wijayanti; Setyo Dwi Santoso (Jurnal SainHealth, 2024)
HbA1C is glycosylated hemoglobin at the N-terminal group, HbA1C is hemoglobin with a minor component closely related to blood glucose. HbA1C is referred to as the breakdown of sugar in the body's metabolism or glycosylated hemoglobin or glycohemoglobin. HbA1C has several examination methods such as the Boronate Affinity method and Nephelometry Photometry. The two main concepts of HbA1C measurement are based on the separation of hemoglobin fractions and chemical reactions. Both of these methods offer a fast, simple, precise and accurate alternative to the currently used methods and provide substantial freedom from many common hassles. This type of research is comparative analytic experimental. In this study, 25 samples were used during the November-January 2023 period. The purpose of this study was to evaluate the results of the HbA1C examination using two methods. In this study it was concluded that based on the Independent T Test it showed the results of Sig 0.913 > ? (0.05) so that it could be concluded that there was no significant difference in the results of the two examination methods Keywords : HbA1C, Boronate Affinity, Nephelometry Photometry